The marketing strategies of Serbian honey producers - Zarić, Vlade; Vasiljević, Zorica; Nedić, Nebojša; Petković, Danijela (Applied Studies in Agribusiness and Commerce, 2013)
Serbian honey producers are exposed to the increased international competition of recent years. To face up to the new changes, producers are progressively using diversification strategies, such as direct sales and production diversification. The direct sales strategy allows the producers to increase the product added value, while diversification aims to offer new products to the consumers. The aim of this paper is to analyse the honey marketing strategy of Serbian honey producers. The first part of the paper analyses the structure of production costs, production performances as well as the determinants of the honey supply. In the second part of the paper, analysis is focused on the determinants of direct sales. Finally, in the third part of the paper, diversification strategies are discussed. The data for this research has been obtained on the basis of a representative sample consisting of 84 Serbian honey producers interviewed in 2011 and 2012. The results show that the Serbian honey producers operate with more or less similar production costs and with production performances that do not differ significantly. They use direct marketing for two reasons: firstly, it affords personal contact with consumers, and secondly, they aim to decrease the transaction costs, thereby keeping a higher share of the product’s final value. Offering new products to consumers is an attempt to create additional product demand.